Mortality studies: little did we know? / Nurul Aityqah Yaacob - Yaacob, Nurul Aityqah (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2021)
Why do we study mortality? Mortality registration is mandatory in almost all countries and hence mortality studies offer a valuable measure for assessing our community health status. Improving mortality in population will lead to improvements in public health, medical advances, lifestyle changes, and government regulation. No doubt, mortality studies play a very significant role in numerous areas such as the pension systems, insurance sectors, actuarial, demographics and epidemiological research. As an example, actuaries applied mortality forecasts for cash flow projections and assessment of premium and reserves in life insurance and pension. Mortality studies contain modeling mortality plus mortality forecasts. When studying mortality, a useful framework is the difference in mortality rates between clusters. A differential between two groups is simply measured if the groups vary by a fixed characteristic such as sex or age. According to Tuljapurkar & Shripad 1998), there have five characteristics to consider in the mortality studies, which are marital status, sex, racial and ethnic, education and social-economic variables and also genetic variation.